The Food Colloid Principle in the Design of Elderly Food. Issue 4 (8th July 2016) - Nishinari, Katsuyoshi; Takemasa, Makoto; Brenner, Tom; Su, Lei; Fang, Yapeng; Hirashima, Madoka; Yoshimura, Miki; Nitta, Yoko; Moritaka, Hatsue; Tomczynska‐Mleko, Marta; Mleko, Stanisław; Michiwaki, Yukihiro
Abstract: It is necessary to control the rheological properties of bolus to prevent aspiration. To know the risk of aspiration for each person with difficulty in mastication and swallowing, it will be effective to use a test fluid which enables doctors to judge the safe range of the viscosity based on videofluorography. Since the knowledge of dominant factors which govern rheology is required, effects of shear rate, cooling rate, concentration of polysaccharides, coexisting seasonings on viscosity and viscoelasticity are overviewed. Since chemical senses are also known to affect the swallowing behavior, the relation between texture and flavor release is described briefly. Mixture of polysaccharides, proteins and fluid gels are overviewed as texture modifiers. Acoustic analysis of swallowing, extrusion method, a falling needle viscometer, tribological study on frictional coefficient of bolus are also described as each method is expected to be a useful tool to understand the complicated aspect of the disorder in mastication and deglutition. Mastication and swallowing of minced foods and model food gels are also described. Finally, the importance of the communication and collaboration between different disciplines is emphasized. Practical Applications: Polysaccharides have been used to modify the texture of foods. It is necessary to know how these polysaccharides influence the swallowing behavior to design foods for elderly. Since the texture of foods is influenced by taste, aroma and conversely these are influenced by texture, the knowledge on the relation between texture and flavor release is crucial to manipulate the foods to reduce the risk of aspiration. Some examples which are expected to be helpful to design foods for elderly are shown.